Managing today's news media audience first - Husni, Samir; Wenger, Debora Halpern; Price, Hank (Los Angeles CQ Press, and imprint of SAGE Publications, Inc., 2016)
Offers students practical solutions on how to cope with and adapt to the evolving media landscape. This book includes real-world case studies, important theoretical grounding, and a focus on understanding rather than resisting the customer's desire for choice.
Includes bibliographical references (pages 203-210) and index.
Keywords: Broadcast journalism; Television viewers